LANGUAGE AWARENESS: LANGUAGE USE AND REASONS FOR CODE-SWITCHING - Astuti, Cresensiana Widi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
The co-existence of languages in a speech community prompts language users to do code-switching in communication. They do it for certain reasons. This paper is to report language awareness among language users and the reasons why people do code-switching in their speech communities. Using an open-ended questionnaire, this research involved 50 participants. They were asked to identify the languages they had in their repertoire, the language they used when they communicate with certain people, and the reasons why they did code-switching in communication. The results showed that, first, the participants had awareness of languages in their repertoire, namely Indonesian, a local language, and English. Second, they admitted that they did code-switching in communication. Thirdly, the reasons for code-switching were to discuss a particular topic, to signal a change of dimension, to signal group membership, and to show affective functions.DOI: doi.org/10.24071/llt.2020.230109